Comparison of Effectiveness between Rifampicin Ofloxin-Minocycline Regimen and Multidrug Therapy-World Health Organization in Multibacillary Leprosy Patients - Moestopo, Octawyana; Gunawan, Hendra; Dahlan, Anisah (Althea Medical Journal, 2016)
Background: Multidrug therapy (MDT) which is recommended by the World Health Organization (WHO) for multibacillary (MB) leprosy patients has some side effects; it is given in 12 doses over 12-18 months. Patients who refuse or are contraindicated in undertaking MDT-WHO can be given alternative rifampicin-ofloxacin-minocycline (ROM) regimen for 24 months, whose side effects are less but more expensive. This study was conducted to compare the effectiveness between ROM and MDT-WHO regimen in the first 12 months based on the derivation in morphological index (MI) of acid-fast bacilli (AFB) in MB leprosy patient.Methods: This was an observational analytical study with retrospective cohort method. Data was collected from medical records of MB leprosy patients in the Medical Record Installation and Morbus Hansen Clinic, Dr. Hasan Sadikin General Hospital Bandung. The overall derivation in MI in 12 months was assessed according to the type of therapy undertaken by the patient. Data was analyzed by Mann-Whitney U Test.Results: A total of 59 data were selected out of 800 data of new leprosy patients based on the inclusion and exclusion criteria. Among those, 20 patients were treated by ROM and 39 by MDT-WHO. Derivation of MI occurred among both groups, but ROM regimen had higher percentage (94.83%) compared with MDT-WHO regimen (79.57%) with p value=0.003 (p <0.05). Conclusions: ROM regimen has better effectiveness than MDT-WHO regimen in the first 12 months in MB leprosy patients. [AMJ.2016;3(4):661â5]DOI:Â 10.15850/amj.v3n4.955